2005
DOI: 10.1088/0953-4075/38/8/002
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation dynamics of doubly excited states of molecular hydrogen

Abstract: The experimental cross sections for the various decay channels of the doubly excited states of H2 after photon absorption have been modelled as a superposition of scaled absorption profiles. Limits of the adiabatic hypothesis for the dissociation of these states were put into evidence, and some non-adiabatic mixings could be quantified. The various dissociation channels have been identified, state by state, and the various dissociation yields determined when the dipole moment was known.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 23 publications
4
38
0
Order By: Relevance
“…The most signifi cant disagreements occur with the Hα results, where the high-energy secondary maxima observed experimentally are, in comparison with the low-energy peak, signifi cantly larger than in the calculated cross sections. It is important to note that channel (3) resonant Q3 (2sσ g ) doubly excited state excitation-which is required for reasonable heuristic fi ts to the Hα data [6,16]-is predicted to be small-to-negligible on the basis of our ab initio theory (see also [5]). …”
Section: Data and Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The most signifi cant disagreements occur with the Hα results, where the high-energy secondary maxima observed experimentally are, in comparison with the low-energy peak, signifi cantly larger than in the calculated cross sections. It is important to note that channel (3) resonant Q3 (2sσ g ) doubly excited state excitation-which is required for reasonable heuristic fi ts to the Hα data [6,16]-is predicted to be small-to-negligible on the basis of our ab initio theory (see also [5]). …”
Section: Data and Discussionmentioning
confidence: 93%
“…As mentioned above, photodissociation from doubly excited states competes with ionization and autoionization. However, previous attempts [3,4,6,[13][14][15][16] to evaluate the photodissociation cross section σ d have made use of the simple empirical formula σ d (E) = χ d σ a (E), where σ a is the absorption cross section evaluated in the Franck-Condon approximation and χ d is the dissociation yield or survival probability. The latter quantity has been either estimated [13] or calculated semiclassically [3,4] assuming that it is independent of the photon energy.…”
Section: Introductionmentioning
confidence: 99%
“…11 yielded lifetimes of (2.9270.15) ns and of (2.8270.16) ns, notably higher than the literature value. Regarding calculated data from [12], the radiative H(2p) state in both of the hydrogen atoms is not only occupied directly after the dissociation, but also from H(nl) states like 3s and 3p. Therefore, a fit function consisting of three fixed lifetimes taken from [13], 1.6 ns (2p-1s transition), 15.6 ns (3d-2p) and 156.7 ns (3s-2p), has been created, convolved with a Gaussian function that corresponds to the time resolution of the set-up.…”
Section: Set-up Performancementioning
confidence: 97%
“…They found that the states which photodissociate in H(2s) are the 1Q 1 1 + u and the 1Q 2 1 u . On the other hand, Glass-Maujean et al [37] modeled experimental cross section data in order to quantify the competition between the various decay channels and to try to get information on the dynamics of the different doubly excited states. To build up the H(2s) cross section, they used the contributions of the 2Q 1 the (4, 5) Q 2 1 u gives a bigger contribution for the cross section.…”
Section: Fast H(2s) Atomsmentioning
confidence: 99%